Common dysmorphic oocytes and embryos in assisted reproductive technology laboratory in association with gene alternations. (November 2022) - Xu, Murong; Wu, Waner; Zhao, Mingpeng; Chung, Jacqueline Pui Wah; Li, Tin Chiu; Chan, David Yiu Leung
Abstract: Amorphic or defected oocytes and embryos are commonly observed in assisted reproductive technology (ART) laboratories. It is believed that a proper gene expression at each stage of embryo development contributes to the possibility of a decent-quality embryo leading to successful implantation. Many studies reported that several defects in embryo morphology are associated with gene expressions during in vitro fertilization (IVF) treatment. There is lacking literature review on summarizing common morphological defects about gene alternations. In this review, we summarized the current literature. We selected 64 genes that have been reported to be involved in embryo morphological abnormalities in animals and humans, 30 of which were identified in humans and might be the causes of embryonic changes. Five papers focusing on associations of multiple gene expressions and embryo abnormalities using RNA transcriptomes were also included during the search. We have also reviewed our time-lapse image database with over 3000 oocytes/embryos to show morphological defects possibly related to gene alternations reported previously in the literature. This holistic review can better understand the associations between gene alternations and morphological changes. It is also beneficial to select important biomarkers with strong evidence in IVF practice and reveal their potential application in embryo selection. Also, identifying genes may help patients with genetic disorders avoid unnecessary treatments by providing preimplantation genetic testing for monogenic/single gene defects (PGT-M), reduce embryo replacements by less potential, and help scientists develop new methods for oocyte/embryo research in the near future.